Legal Reform of Carbon Trading Mechanisms in Indonesia’s Environmental Law Policy - Zulfikri Akramul Akbar; Ade Wahyuni Azhar; Erniati Erniati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the structural weaknesses of Indonesia’s carbon trading governance within environmental law, investment regulation, and international climate obligations. The research applies normative juridical, doctrinal, and comparative legal approaches through statutory interpretation and conceptual analysis of Indonesian environmental regulations, carbon market regulations, and international climate instruments. The analysis demonstrates that Indonesia’s carbon trading framework remains fragmented because institutional coordination, emissions verification, market supervision, and liability mechanisms are regulated through disconnected legal regimes lacking integrated enforcement structures. The study further identifies serious deficiencies concerning administrative accountability, judicial enforcement, ecological supervision, and climate related financial governance, particularly regarding carbon fraud, greenwashing, and anti money laundering safeguards. Comparative examination of China, Finland, Sweden, and New Zealand illustrates that integrated climate governance requires centralized supervision, transparent carbon registries, enforceable liability systems, and judicially supported environmental accountability. This study proposes an integrated legal reform model emphasizing institutional synchronization, sustainable finance governance, ecological justice, and conformity with the Paris Agreement and United Nations climate regime. The proposed framework strengthens regulatory coherence and climate legitimacy globally.